The Use of Student Profile Books in Monitoring Students' Qur'an Memorization - Friska Putri Purwitasari; Muhammad Satir; Hermanto Hermanto (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Memorizing the Qur’an is a vital activity in Islamic education, fostering students’ spiritual values, discipline, and learning responsibility. However, the monitoring of memorization often lacks systematic instruments. This study aims to analyze the implementation of the student profile book in monitoring the Qur’an memorization of ninth-grade students at MTs Sains Algebra, Sorong City, and and its impact on monitoring students' memorization. The research employs a descriptive qualitative approach, collecting data through observation, interviews, and documentation involving teachers, students, and parents. Data were analyzed through reduction, presentation, and conclusion drawing. The results indicate that the student profile book was developed to meet the school’s need for a structured system to monitor memorization and to engage parents in continuing the learning process at home. The book is designed to be simple, clear, and easy to understand, involving all relevant parties. In practice, students submit their memorization to the class teacher according to a set schedule, and the book is periodically handed over to parents. Its implementation enhances structured monitoring, improves memorization quality, discipline, motivation, and strengthens collaboration between the school and parents. The study implies that the student profile book is an effective evaluative, collaborative, and strategic tool for supporting Qur’an learning in schools.